2023
DOI: 10.3389/fpsyt.2023.1160715
|View full text |Cite
|
Sign up to set email alerts
|

Core of sensory gating deficits in first-episode schizophrenia: attention dysfunction

Abstract: BackgroundSensory gating deficits are a common feature of schizophrenia and may be indicative of higher-order psychopathological impairments. It has been proposed that incorporating subjective attention components into prepulse inhibition (PPI) measures may improve the accuracy of assessing these deficits. This study aimed to investigate the relationship between modified PPI and cognitive function, with a specific focus on subjective attention, to gain a better understanding of the underlying mechanisms of sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“… 9 Using the perceived spatial separation (PSS-PPI) paradigm — whereby the leading ear given background noise is different from the ear receiving the prepulse stimulus — a study found that the PSS-PPI positively correlated with the speed of processing, attention or vigilance and social cognition in unmedicated, first-episode schizophrenia. 25 Among patients with BD, the language domain of the Repeatable Battery for the Assessment of Neuropsychological Status positively correlated with both the PSS-PPI and the perceived spatial co-location (PSC-PPI, in which the leading ear given background noise is the same ear receiving the prepulse stimulus). 26 In the same study, double word time and colour interference time negatively correlated with the PSS-PPI.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Using the perceived spatial separation (PSS-PPI) paradigm — whereby the leading ear given background noise is different from the ear receiving the prepulse stimulus — a study found that the PSS-PPI positively correlated with the speed of processing, attention or vigilance and social cognition in unmedicated, first-episode schizophrenia. 25 Among patients with BD, the language domain of the Repeatable Battery for the Assessment of Neuropsychological Status positively correlated with both the PSS-PPI and the perceived spatial co-location (PSC-PPI, in which the leading ear given background noise is the same ear receiving the prepulse stimulus). 26 In the same study, double word time and colour interference time negatively correlated with the PSS-PPI.…”
Section: Introductionmentioning
confidence: 99%